Nyi Roro Kidul's Representation in Mobile Legends: (Bang Bang) A Semiotic Study - Nabila Shauma Lutfia; Elvi Citraresmana; Muhamad Adji (Eduvest - Journal of Universal Studies, 2026)
This research examines the representation of Nyi Roro Kidul in the character Kadita from the game Mobile Legends: Bang Bang using Roland Barthes' semiotic approach and Stuart Hall's theory of representation. Nyi Roro Kidul, a mythological figure revered by the Javanese people as the ruler of the South Sea, is reimagined as a digital game character. The objects of analysis include verbal signs, all of the character's spoken lines, and visual signs, such as costume, color, attributes, and the visual effects of Kadita's abilities. This research uses a qualitative descriptive method with documentation and direct observation techniques. The analysis applied Barthes' three levels of meaning denotation, connotation, and myth supported by Hall's encoding-decoding theory of representation. The findings show that Kadita's representation of Nyi Roro Kidul is constructed through a synergy of verbal and visual signs that preserve key markers of cultural identity, such as the dominant use of green, the crown, and associations with the sea, while simultaneously undergoing an aesthetic transformation into an anime-style fantasy character defined by active combat. Verbal signs, particularly imperative speech patterns, construct Kadita as a ruler with absolute authority over the ocean, while the myth that emerges reproduces Javanese cosmological beliefs regarding the South Sea as a sacred domain. The study concludes that Kadita represents an adaptive mytha reconstruction of the Nyi Roro Kidul figure shaped to meet the demands of the global digital gaming industry.